EFEKTIVITAS EKSTRAK METANOL DAUN KETEPENG CINA (Cassia alata L.) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Staphylococcus epidermidis SECARA TUNGGAL DAN KOMBINASI - Annisa Putri Hanifa; Dina Erliana; Avidlyandi Avidlyandi; Meika Rizka; Deni Agus Triawan; Sal Prima Yudha S; Morina Adfa (LP4MK STKIP PGRI Lubuklinggau, 2022)
The aim of this study was to determine the antibacterial activity and the ccombined effect of methanol extract of the ketepeng cina leaves (Cassia alata L.) with six selected plant extracts against Staphylococcus epidermidis using the diffusion and the paper strip methods at a concentration of 10% w/v. The results showed the average antibacterial activity of each extract showed the inhibitory growth of Staphylococcus epidermidis. The average value of the inhibition zones of the single extract samples of ketepeng cina, sambang darah, ruku-ruku, avocado seed, bungli, pacar air, and sungkai resulted in inhibition zones of 6.28±0.20 mm, 7.90±0.31 mm, 2.30±0.37 mm, 3,53±0.50 mm, 4.35±0.52 mm, and 4.69±0.17 mm, respectively. Furthermore, the combination of methanol extract of ketepeng cina leaves (C. alata) with the six selected plants extract in an average diameter of inhibition zone greater than the average diameter of the inhibition zone of each extract. However, the average diameter of the inhibition zone of the combined extract was not more significant than the sum of the diameter of the inhibition zone of each extract. The conclusion of this study is the combination of the methanol extract of ketepeng cina leaves (C. alata) with six selected plant extracts has an additive/indifferent effect in inhibiting the growth of S. epidermidis.